PENGUNGKAPAN DIRI (SELF DISCLOSURE) PADA ORANG DENGAN HIV/AIDS (ODHA) - I Wayan Candra; Ayu Gede Intan Astri Dewi (Poltekkes Kemenkes Jakarta III, 2017)
HIV/AIDS is public health problems the largest in the world today.HIV/AIDS there are in almost all countries in the world without exception including indonesia. A person who is infected with HIV/AIDS or living still have fear to express status disease because of the stigma the negative of the community of HIV/AIDS. The disclosure of self ( self disclosure ) is the type a communication that revealed information about yourself to others who actively hidden. Self disclosure can help someone communicate with others, increase the confidence of ourselves and relation of being more familiar.Self disclosure also be able to deliver the guilt and anxious. This study attempts to know the level disclosure everybody with HIV/AIDS in health foundation Bali.The kind of research this is research descriptive. This research used the cross sectional. Sampling techniques used is purposive sampling. The total sample of the research is 30 people.Using techniques data collection jourard self disclosure quitionaire . The result showed 5 respondents (16.7%) has a high disclosure themselves, 19 respondents (63.3 %) have a themselves are disclosure, and 6 respondents (20%) have a low disclosure themselves. Most of the disclosure themselves (self disclosure) among respondents is the disclosure themselves are about 19 respondents (63.3%).